The histone methyltransferase Ezh2 restrains macrophage inflammatory responses. Issue 10 (31st August 2021) - Kitchen, Gareth B.; Hopwood, Thomas; Gali Ramamoorthy, Thanuja; Downton, Polly; Begley, Nicola; Hussell, Tracy; Dockrell, David H.; Gibbs, Julie E.; Ray, David W.; Loudon, Andrew S. I.
Abstract: Robust inflammatory responses are critical to survival following respiratory infection, with current attention focused on the clinical consequences of the Coronavirus pandemic. Epigenetic factors are increasingly recognized as important determinants of immune responses, and EZH2 is a prominent target due to the availability of highly specific and efficacious antagonists. However, very little is known about the role of EZH2 in the myeloid lineage. Here, we show EZH2 acts in macrophages to limit inflammatory responses to activation, and in neutrophils for chemotaxis. Selective genetic deletion in macrophages results in a remarkable gain in protection from infection with the prevalent lung pathogen, pneumococcus. In contrast, neutrophils lacking EZH2 showed impaired mobility in response to chemotactic signals, and resulted in increased susceptibility to pneumococcus. In summary, EZH2 shows complex, and divergent roles in different myeloid lineages, likely contributing to the earlier conflicting reports. Compounds targeting EZH2 are likely to impair mucosal immunity; however, they may prove useful for conditions driven by pulmonary neutrophil influx, such as adult respiratory distress syndrome.